A Sample WebQuest Applicable in Teaching Topological Concepts - Yildiz, Sevda Goktepe; Korpeoglu, Seda Goktepe (NECMETTIN ERBAKAN UNIV, 2016)
In recent years, WebQuests have received a great deal of attention and have been used effectively in teaching-learning process in various courses. In this study, a WebQuest that can be applicable in teaching topological concepts for undergraduate level students was prepared. A number of topological concepts, such as countability, infinity, and sets were incorporated into the WebQuest developed. The WebQuest consists of six stages: introduction, task, process, resources, evaluation and conclusion. After the WebQuest activity was applied, the usability of the WebQuest was evaluated, taking into account students' views. The study was carried out with 29 elementary mathematics pre-service teachers. The data was collected in written form using an interview form that was developed by the researchers. The results indicated that the pre-service teachers have not previously encountered such WebQuest activities however; they display a keen interest in learning about this technology-aided activity and the opportunities to use it in their further lessons.
Keywords: Mathematics education; Pre-service teachers; Topological concepts; WebQuest; SCHOOL; Education & Educational Research